Pulling threads together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A symposium on the cotton sector in West and central Africa, organised in Ouagadougou, Burkina Faso in July 2000 by the region s Conference of Ministers of Agriculture (CMA/WCA)